Draw solutions for forward osmosis processes: Developments, challenges, and prospects for the future - Ge, Qingchun; Ling, Mingming; Chung, Tai-Shung (Journal of membrane science, 2013)
Forward osmosis (FO) has emerged as one of potential technologies to mitigate clean water and energy shortage. Not only can it produce clean water but also energy by employing draw solutes to induce osmotic gradients across semipermeable membranes as the driving force for water production and power generation. Ideally, the semipermeable membrane performs as a barrier that allows only water to pass through but rejects all others. However, in reality, depending on draw solute's chemistry property and physical structure, the reverse flux of draw solutes may take place across FO membranes which not only results in a lower effective osmotic driving force but also facilitates fouling. In addition, the asymmetric structure of FO membranes and the transport resistance of draw solutes within the FO membranes cause concentration polarization and lower the water flux. Furthermore, the regeneration of draw solutes from diluted draw solutions and the production of clean water might be energy-intensive if inappropriate draw solutes and recycle processes are utilized. Therefore, in this work we aim to give a comprehensive review on the progress of draw solution for FO processes. An assessment on the advantages and limitations of the existing draw solutes are made. Various FO integrated processes for water production and draw solute regeneration are exemplified. We also highlight the challenges and future research directions for the molecular design of better draw solutes. •Forward osmosis processes: potential technologies to mitigate water and energy shortage.•Draw solutions: one of the two key factors in affecting FO technology.•Draw solutions: developments, challenges, and prospects for the future.